Hubungan Tingkat Pengetahuan dengan Sikap Remaja Terhadap Penyalahgunaan Napza di Sma Katolik Rantepao: The Relationship Between Knowledge Level and Youth Attitudes Towards Drug Abuse in Catholic High School Rantepao - Beda, Nikodemus Sili (Stikes Wira Medika Bali, 2020)
Adolescence is a transitional period, where at this time adolescents are looking for identity as a teenager and trying to achieve independence by relying on their knowledge to try new things that sometimes deviate from society's norms.Therefore, it is hoped that adolescents have knowledge and a good attitude to avoid negative things such as drug abuse, which has a negative impact both physically, psychologically and socially. The purpose of this study was to determine the relationship between knowledge and attitudes of adolescents against drug abuse in Catholic High Schools equated to North Rantepao Toraja. This research was conducted in February 2020. This type of research is a correlation with the croos sectional approach. The study population was all Catholic high school students equal to Rantepao Toraja Utara and the sampling technique was probabilty sampling using a proportionate stratified random sampling approach, with a sample size of 100 respondents. Data collection using a questionnaire. The statistical test used is the Chi Square statistical test using the alternative test of Continuity correction with the SPSS. Thus, it can be concluded that there is no significant relationship between the level of knowledge of adolescents and adolescent attitudes towards drug abuse in Catholic High Schools compared to North Rantepao Toraja. In general, attitudes are determined by knowledge, but patterns of thought, beliefs and emotions play an important role in determining a person's attitude.